2006
DOI: 10.1152/japplphysiol.01380.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for the control of respiratory evaporative heat loss in panting animals

Abstract: Panting is a controlled increase in respiratory frequency accompanied by a decrease in tidal volume, the purpose of which is to increase ventilation of the upper respiratory tract, preserve alveolar ventilation, and thereby elevate evaporative heat loss. The increased energy cost of panting is offset by reducing the metabolism of nonrespiratory muscles. The panting mechanism tends to be important in smaller mammalian species and in larger species is supplemented by sweating. At elevated respiratory frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
117
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 37 publications
6
117
0
5
Order By: Relevance
“…Loss of heat by utilization of the latent heat of vaporization of water is an important component of the spectrum of physio logical strategies available to species that control their body temperature in the face of variable thermal loads (Robertshaw, 2006). According to Mitlöhner et al (2002) heat stressed cattle could increase water and feed intake, stand rather than lie down, increase respiration rate and body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heat by utilization of the latent heat of vaporization of water is an important component of the spectrum of physio logical strategies available to species that control their body temperature in the face of variable thermal loads (Robertshaw, 2006). According to Mitlöhner et al (2002) heat stressed cattle could increase water and feed intake, stand rather than lie down, increase respiration rate and body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…MW have a dense dorsal pelage, and when lying in the daytime shade, they pant like other canids, tongue hanging out and dripping. Thermal panting is costly in water loss: up to 50 mL/h in 25 kg dogs at 40°C (Blatt et al, 1972); but paradoxically, it is an energy-neutral behavior (Robertshaw, 2006). Dogs (25 kg) began to secrete water from the nasal glands for panting at 30°C (Blatt et al, 1972), which is exactly the temperature at which MW cease activity (Figure 2.2).…”
Section: Resting Sitesmentioning
confidence: 99%
“…IN MANY SPECIES of mammals and birds, an elevation in body temperature stimulates ventilation and increases evaporative heat loss for thermoregulation (the so-called panting response) (42). In 1905, Haldane (25) was the first to report that hyperthermia also increases ventilation in humans, and the recent review by White (53) suggested that the hyperthermic hyperventilatory response provides countercurrent cooling of blood perfusing the brain (selective brain cooling).…”
mentioning
confidence: 99%